2011
DOI: 10.1167/iovs.11-8050
|View full text |Cite
|
Sign up to set email alerts
|

Association between Depression and Dry Eye Disease in an Elderly Population

Abstract: Depression was associated with DED symptoms in subjects with normal or mildly reduced tear production.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
114
1
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 138 publications
(131 citation statements)
references
References 42 publications
13
114
1
3
Order By: Relevance
“…This agrees with previous studies in which DED had a negative effect on mental health (Mertzanis et al 2005;Galor et al 2011;Kim et al 2011;Le et al 2012;Li et al 2012;Wang et al 2012;Sakane et al 2013). The study on a non-clinic-based population in China showed lower QOL for mental health in subjects with DED (Le et al 2012).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…This agrees with previous studies in which DED had a negative effect on mental health (Mertzanis et al 2005;Galor et al 2011;Kim et al 2011;Le et al 2012;Li et al 2012;Wang et al 2012;Sakane et al 2013). The study on a non-clinic-based population in China showed lower QOL for mental health in subjects with DED (Le et al 2012).…”
Section: Discussionsupporting
confidence: 91%
“…The study on a non-clinic-based population in China showed lower QOL for mental health in subjects with DED (Le et al 2012). In a survey of the general population aged ≥ 65 years in Korea, the DED Group had a higher rate of depression compared with the Non-DED Group (Kim et al 2011). Wang et al (2012) demonstrated significantly higher prevalence of comorbidity in patients with depression and DED in Taiwan.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…77 Others studies in Asian populations have described similar relationships between depression and dry eye. [78][79][80] Hypersensitivity to other stimuli and the development of diffuse pain states can also be seen with central sensitization, 74 and again these features have been described in dry eye. Data from the national VA database demonstrated that patients with chronic pain diagnoses (ICD-9 codes 338.29, 724.2, 724.5, 338.4, and 338.28) were 1.9 times more likely to carry a dry eye diagnosis compared with their counterparts without chronic pain (odds ratio (OR) 1.89, 95% confidence interval (CI) 1.88-1.90).…”
Section: Central Sensitization and Chronic Dry Eye Symptomsmentioning
confidence: 79%
“…Although evaluation of tear volume is indispensable for dry eye diagnosis, precise measurement is difficult because of the tiny amount and transparency of tears. It is known that tear volume is affected by environmental, physical and psychological situations, such as humidity, wearing contact lenses, being engaged in VDT work and having mental stress [2,3]. At the clinical site, tear evaluation is usually performed by either schirmer's test or tear breakup time (BUT) measurement.…”
Section: Introductionmentioning
confidence: 99%